Vascular endothelial growth factor biology for regenerative angiogenesis (Swiss Medical Weekly, 2019)
Despite major advances in medical, catheter-based or surgical treatment, cardiovascular diseases such as peripheral artery disease and coronary artery disease still cause signiﬁcant morbidity and mortality. Furthermore, many patients do not qualify for catheter-based treatment or bypass surgery because of advanced disease or surgical risk. There is therefore an urgent need for novel treatment strategies. Therapeutic angiogenesis aims to restore blood flow to ischaemic tissue by stimulating the growth of new blood vessels through the local delivery of angiogenic factors, and may thus be an attractive treatment alternative for these patients. Angiogenesis is a complex process and the growth of normal, stable and functional vasculature depends on the coordinated interplay of different cell types and growth factors. Vascular endothelial growth factor-A (VEGF) is the fundamental regulator of vascular growth and the key target of therapeutic angiogenesis approaches. However, first-generation clinical trials of VEGF gene therapy have been disappointing, and a clear clinical benefit has yet to be established. In particular, VEGF delivery (a) appears to have a very limited therapeutic window in vivo: low doses are safe but mostly inefficient, whereas higher doses become rapidly unsafe; and (b) requires a sustained expression in vivo of at least about four weeks to achieve stable vessels that persist after cessation of the angiogenic stimulus. Here we will review the current understanding of how VEGF induces the growth of normal or pathological blood vessels, what limitations for the controlled induction of safe and efficient angiogenesis are intrinsically linked to the biological properties of VEGF, and how this knowledge can guide the design of more effective strategies for therapeutic angiogenesis.